2015
DOI: 10.1177/2158244015585999
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Silent and Freeze-Frame Viewing Techniques of Video Materials on the Intermediate EFL Learners’ Listening Comprehension

Abstract: The use of modern technologies has been widely prevalent among language learners, and video, in particular, as a valuable learning tool provides learners with comprehensible input. The present study investigated the effect of silent and freezeframe viewing techniques of video materials on the intermediate English as a foreign language (EFL) learners' listening comprehension. To this end, 45 intermediate EFL learners participated in this quasi-experimental study. The results of one-way ANOVA revealed that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…It provides original and authentic input for students as they are produced originally for native speakers (Bajrami & Ismaili, 2016). Moreover, it also provides a real language expression with cultural information of target language learned by the students (Shahani & Tahriri, 2015). It enhances the language teaching and learning activities and the students generally felt that technology is useful for learning ESL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides original and authentic input for students as they are produced originally for native speakers (Bajrami & Ismaili, 2016). Moreover, it also provides a real language expression with cultural information of target language learned by the students (Shahani & Tahriri, 2015). It enhances the language teaching and learning activities and the students generally felt that technology is useful for learning ESL.…”
Section: Introductionmentioning
confidence: 99%
“…Video has become as a teaching resource in language teaching and learning process since 1970s (Bal-Gezegin, 2014) and still being used nowadays in many English classroom. It has been categorized as an interesting media (Bajrami & Ismaili, 2016;Shahani & Tahriri, 2015) which creates a meaningful learning for students (Bajrami & Ismaili, 2016;Marefat & Hassanzadeh, 2014) since it provides both appropriate visual and audio input for the students (Bal-Gezegin, 2014;Gowhary, et al, 2014;Marefat & Hassanzadeh, 2014;Shahani & Tahriri, 2015). Thus, the students can observe specific facial expressions (Bal-Gezegin, 2014;Safarali & Hamidi, 2012), gestures (Safarali & Hadi Hamidi, 2012), and emotional attitudes (Bajrami & Ismaili, 2016) shown by the speakers in the video.…”
Section: Video In English Teaching and Learning Processmentioning
confidence: 99%
“…Hsu (2011) believes that having multimedia technology can be useful to improve writing abilities in classes. It should also be considered that video can provide learners with content, context, and language (Shahani & Tahriri, 2015); therefore, using it would be interesting for them. It can also be concluded that having funny animated pictures can result in higher…”
Section: Testing the Null Hypothesismentioning
confidence: 99%
“…Researchers in the field of listening comprehension highlight the importance of following an appropriate of pre-, while-and post-pedagogical cycle of listening instruction (Vandergrift, 2003a;Vandergrift, 2003b;Kra-jka, 2006;Cross, 2009); incorporation of bottom-up activities (Siegel & Siegel, 2015); teaching metacognitive listening strategies (Kurita, 2012;An & Shi, 2013;Zarrabi, 2016); using metacognitive activities in classroom (Goh, 2014;Elk, 2014); and applying different techniques for listening comprehension using videos (Shahani & Tahriri, 2015). Other suggestions for teachers who use audio-visual materials that can be applied to a CLIL context include the following: • Authentic videos should be carefully chosen to minimize difficulties with language comprehension and interest in content (Kim, 2015);…”
Section: Clil and Foreign Language Learningmentioning
confidence: 99%